2018
DOI: 10.1186/s40349-018-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial and pulsed focused ultrasound that activates brain can accelerate remyelination in a mouse model of multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) impacts approximately 400,000 in the United States and is the leading cause of disability among young to middle aged people in the developed world. Characteristic of this disease, myelin within generally focal volumes of brain tissue wastes away under an autoimmune assault, either inexorably or through a cycle of demyelination and remyelination. This centrally located damage produces central and peripheral symptoms tied to the portion of brain within the MS lesion site. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Mathematical modeling suggests that LIFUS may activate sodium, calcium, and potassium channels [ 85 ], and might produce action potentials in neurons [ 85 ]. The application of a mechanical force improves electrical transmission through a damaged axon, which might be associated with nerve regenerating [ 75 ] and remyelinating [ 86 ] effects elicited by FUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling suggests that LIFUS may activate sodium, calcium, and potassium channels [ 85 ], and might produce action potentials in neurons [ 85 ]. The application of a mechanical force improves electrical transmission through a damaged axon, which might be associated with nerve regenerating [ 75 ] and remyelinating [ 86 ] effects elicited by FUS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, LIFUS (360-760 mW/cm 2 ) activates the cerebral cortex as measured by c-Fos expression [ 91 , 92 ] (Fig. 2 ) and electroencephalography [ 86 ]. Further studies agree with this excitatory effect [ 24 , 85 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subject Response Rate Sliding Window Analysis A binary coding system was applied to the participant response of observed percepts at each trial (Fry et al, 1955;Velling and Shklyaruk, 1988;Tyler et al, 2008;Tufail et al, 2010;Min et al, 2011;Yoo et al, 2011aYoo et al, ,b, 2018Kim et al, 2012Kim et al, , 2014Deffieux et al, 2013;King et al, 2013;Younan et al, 2013;Mehić et al, 2014;Kamimura et al, 2016;Lee et al, 2016b;Monti et al, 2016;Ye et al, 2016;Airan et al, 2017;Wattiez et al, 2017;Olmstead et al, 2018), using ''1'' to signify a reported percept report and ''0'' for none. The data series was smoothed by passing it through different sliding windows where the average response rate was calculated for bins of four, five, eight, or 10 consecutive trials.…”
Section: Discussionmentioning
confidence: 99%
“…For example, stimulation of the thalamus of anesthetized rats can reduce the time required for them to recover from the anesthesia (Yoo et al, 2011b), while thalamic stimulation of a recently comatose patient produced significant clinical improvement (Monti et al, 2016). Our group has successfully applied nDU to a mouse model of multiple sclerosis, thereby demonstrating accelerated remyelination in mice (Olmstead et al, 2018); another group showed a reduction of acute epileptic seizure activity in rats (Min et al, 2011). Also, nDU application to the thalamus of swine inhibited down-stream sensory evoked potentials (Dallapiazza et al, 2018) with a variety of potential uses.…”
Section: Introductionmentioning
confidence: 99%
“…Epidural electrical stimulation after spinal cord injury also enhanced remyelination and increased OL differentiation and survival ( Li et al, 2020 ). Likewise, brain activation using 20 Hz ultrasound bursts increased remyelination after cuprizone demyelination in mice ( Olmstead et al, 2018 ) and voluntary exercise immediately after lysolecithin lesions of the spinal cord white matter increased OPC proliferation, differentiation and remyelination ( Jensen et al, 2018 ). Notably, pairing voluntary exercise with the pro-myelinating drug clemastine showed an additive effect in increasing myelin repair ( Jensen et al, 2018 ).…”
Section: Modulation Of Neuronal Activity During Remyelinationmentioning
confidence: 99%